The 45th Muhammadiyah Congress Contest between Literal-Conservative and Liberal-Moderate Muslims in Indonesia - Burhani, Ahmad Najib (Studia Islamika, 2005)
Muhammadiyah's 45 Congress, held in Malang, East Java July 3-8, 2005, saw the inauguration of the thirteen new high officials for the Board of Muhammadiyah for the 2005-2010 term. the congress also swore in Muhammadiyah's new leader, Professor Din Syamsuddin. The elections for the second largest Muslim organization in Indonesia were not, however, the focus of this congress. the primary issue of concern was on how this organization would prepare itself to develop futher after one century of existence in Indonesia. the theme of the congress was "Movement for Enlightenment" This congress is projected to be a stepping-stone for the resurgence (kebangkitan) of the organization, which was first established in Jogjakarta in 1912DOI: 10.15408/sdi.v12i1.650